Use of eltrombopag for the treatment of poor graft function after hematopoietic stem cell transplantation in children. (20th March 2021) - Uria‐Oficialdegui, M. Luz; Alonso, Laura; Benitez‐Carabante, M. Isabel; Renedo, Berta; Oliveras, Maria; Diaz‐de‐Heredia, Cristina
Abstract: The main objective of this study was to determine whether Eltrombopag, a synthetic thrombopoietin receptor agonist, could improve peripheral blood counts in the three hematopoietic lineages and achieve transfusion independence in children with poor graft function (PGF) after allogenic hematopoietic stem cell transplantation (HSCT). Retrospective study of patients under 18 years who developed PGF post‐HSCT in a large tertiary institution between January 2013 and March 2019. Out of 198 allogeneic HSCT, five patients met PGF criteria and were treated with eltrombopag. Median time from HSCT to eltrombopag initiation was 120 days. The median starting dose was 50 mg/day and the maximum dose reached was 75 mg/day. Median treatment duration was 9 months. Three patients achieved complete response and one partial response. The median dose among responders was 75 mg/day and the median time to response 8 weeks. Responses were sustained in three patients and two required a booster dose of CD34 + ‐selected cells from the original donor. None of the patients had to stop treatment due to adverse effects. The use of eltrombopag in children with PGF achieved responses in 80% of cases and demonstrated to be an effective and safe therapeutic option in pediatric patients with PGF.